2022
DOI: 10.3389/fpls.2022.920138
|View full text |Cite
|
Sign up to set email alerts
|

The Antarctic Moss Pohlia nutans Genome Provides Insights Into the Evolution of Bryophytes and the Adaptation to Extreme Terrestrial Habitats

Abstract: The Antarctic continent has extreme natural environment and fragile ecosystem. Mosses are one of the dominant floras in the Antarctic continent. However, their genomic features and adaptation processes to extreme environments remain poorly understood. Here, we assembled the high-quality genome sequence of the Antarctic moss (Pohlia nutans) with 698.20 Mb and 22 chromosomes. We found that the high proportion of repeat sequences and a recent whole-genome duplication (WGD) contribute to the large size genome of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…The clean reads were generated and used for the following analysis. Firstly, we performed the alignment program for mapping sequencing reads to the reference genome of P. nutans ( Liu et al, 2022 ). This process was conducted by HISAT2 program, generating a bam format file with index information ( Kim et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The clean reads were generated and used for the following analysis. Firstly, we performed the alignment program for mapping sequencing reads to the reference genome of P. nutans ( Liu et al, 2022 ). This process was conducted by HISAT2 program, generating a bam format file with index information ( Kim et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have found that several gene families were expanded which participated in biosynthesis of metabolites such as fatty acid elongation and alpha-Linolenic acid metabolism ( Liu et al, 2022 ). Here, we found that the content of very-long-chain fatty acids (VLCFAs) increased significantly under cold stress in metabolome analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In land plants, flavonoids serve as signal molecules and antioxidants under stress conditions and have prominent roles regulating plant growth and development [ 48 , 49 ]. Flavonoids, such as flavonols and anthocyanins, emerged sequentially as land plants evolved from aquatic to terrestrial environments, facilitating their adaptation to harsh conditions [ 19 ]. However, the molecular process of flavonoid biosynthesis in bryophytes and basal land plants is largely unknown [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, flavonoids, including flavanols, flavanones, flavones, and flavonols, accounted for 7.25% of the total compounds in P. nutans ( Table S1 ). Under stress conditions, bryophytes can synthesize early colorless UV-B ultraviolet-absorbing substances rather than the down-stream products, such as anthocyanins [ 19 , 51 ]. Flavone and flavonol biosynthesis, however, belong to the early metabolites of flavonoid pathway, and they are catalysed by enzymes of different branching pathways into anthocyanins [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation